Transcriptional regulation of multiciliated cell differentiation. (February 2021) - Lewis, Michael; Stracker, Travis H.
Highlights: GEMC1 and MCIDAS control multiciliated cell differentiation in a stepwise manner. p73 plays a major role in multiciliogenesis. Multiciliated cells activate a cell cycle program to regulate centriole amplification. PLK4, mother centrioles and deuterosomes are not strictly required for multiciliogenesis. Centriole numbers scale to cell surface area. Abstract: Multiciliated cells (MCC) project dozens to hundreds of motile cilia from the cell surface to generate fluid flow across epithelial surfaces or turbulence to promote the transport of gametes. The MCC differentiation program is initiated by GEMC1 and MCIDAS, members of the geminin family, that activate key transcription factors, including p73 and FOXJ1, to control the multiciliogenesis program. To support the generation of multiple motile cilia, MCCs must undergo massive centriole amplification to generate a sufficient number of basal bodies (modified centrioles). This transcriptional program involves the generation of deuterosomes, unique structures that act as platforms to regulate centriole amplification, the reactivation of cell cycle programs to control centriole amplification and release, and extensive remodeling of the cytoskeleton. This review will focus on providing an overview of the transcriptional regulation of MCCs and its connection to key processes, in addition to highlighting exciting recent developments and open questions in the field.